Cerebrospinal fluid Alzheimer biomarkers can be useful for discriminating dementia with Lewy bodies from Alzheimer's disease at the prodromal stage. Issue 5 (10th January 2018) - Bousiges, Olivier; Bombois, Stephanie; Schraen, Susanna; Wallon, David; Quillard, Muriel Muraine; Gabelle, Audrey; Lehmann, Sylvain; Paquet, Claire; Amar-Bouaziz, Elodie; Magnin, Eloi; Miguet-Alfonsi, Carole; Delbeuck, Xavier; et al.
Abstract : Background: Differential diagnosis between dementia with Lewy bodies (DLB) and Alzheimer's disease (AD) is not straightforward, especially in the early stages of disease. We compared AD biomarkers (phospho-Tau181, total-Tau, Aβ42 and Aβ40) in cerebrospinal fluid (CSF) of patients with DLB and AD, focusing especially on the prodromal stage. Methods: A total of 1221 CSF were collected in different memory centres (ePLM network) in France and analysed retrospectively. Samples were obtained from patients with prodromal DLB (pro-DLB; n=57), DLB dementia (DLB-d; n=154), prodromal AD (pro-AD; n=132) and AD dementia (n=783), and control subjects (CS; n=95). These centres use the same diagnostic procedure and criteria to evaluate the patients. Results: In patients with pro-DLB, CSF Aβ42 levels appeared much less disrupted than in patients at the demented stage (DLB-d) (P<0.05 CS>pro-DLB; P<0.001 CS>DLB-d). On average, Aβ40 levels in patients with DLB (pro-DLB and DLB-d) were much below those in patients with pro-AD (P<0.001 DLB groups<pro-AD). The Aβ42/Aβ40 ratio in patients with pro-DLB remained close to that of CS. t-Tau and phospho-Tau181 levels were unaltered in patients with DLB (pro-DLB and DLB-d). Conclusions: Reduced levels of CSF Aβ42 were found in patients with DLB but rather at a later stage, reaching those of patients with AD, in whom Aβ42 levels were decreased even at the prodromal stage. At the prodromal stage of DLB, the majority of patients presented a normal CSF profile. CSF t-Tau and phospho-Tau181 were the best biomarkers to discriminate between AD and DLB, whatever the stage of disease.